Pastoralist refugee crisis tests the resilience of open property regime in the Logone Floodplain, Cameroon. (July 2019) - Moritz, Mark; Garcia, Victoria; Buffington, Abigail; Ahmadou, Mouadjamou
Highlights: Boko Haram refugee crisis nearly doubles grazing pressure in Logone Floodplain. Ideal free distribution in floodplain persists despite arrival of pastoralist refugees. Long-term data on livestock populations indicates resilience of pastoral system. Open access to common-pool resources is key to resilience of open property regime. Abstract: Previous studies have shown that the open property regime of mobile pastoralists in the Logone Floodplain, Cameroon works as a complex adaptive system in which individual movement decisions result in an ideal free distribution of grazing pressure over common-pool grazing resources. Recently, the humanitarian crisis in the Chad Basin caused by Boko Haram has resulted in the arrival of thousands of pastoralist refugees from Northeastern Nigeria in the Far North Region of Cameroon. In this paper, we examine the impact of pastoralist refugees on the resilience of the open property regime. First, we describe the migratory flight of pastoralists. Second, we examine whether and how the pastoralist refugee crisis affected the open property regime, in particular the distribution of pastoralists over grazing resources. Data were collected in a longitudinal and interdisciplinary study that integrated spatial and ethnographic approaches to describe and explain the distribution of pastoralists in the Logone Floodplain from 2008 to 2016. The results show that the number of pastoralist refugees from Nigeria exceeds 1000 households with an estimated 100, 000 cattle. However, despite the large number of pastoralist refugees, we continue to find evidence of an ideal free distribution of pastoralists over grazing resources in the Logone Floodplain. Moreover, we found that pastoralists, while frustrated by the increasing grazing pressure, remained committed to the ethos of open access. The study offers evidence of the resilience of the open property regime and we discuss the reasons for the resilience of this complex adaptive system using the concept of panarchy.